United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Crisis Management Arrangements. (IMF Staff Country Reports; Country Report ;, 2010)
This paper presents a technical note on Crisis Management Arrangements for the United States. The crisis has seen widespread systemic instability, large-scale fiscal support, and an increase in moral hazard. The lack of a formal systematic process for the assessment of risks may have contributed to a slow response to identified risks, but the additional complexity of coordinating interagency actions in response to identified risks did not help. Power to act remained with the individual agencies, and coordinating a response to identified risks could take time.